PELLAGRA IN ASSOCIATION WITH HALLUCINATION AND OVER-SALIVATION - Raef Ahmad M Qutub; Rafif Ghazi Alsaigh; Raheel Ali Al-Harazi; Emtenan Sadaqah Hemmish (International Journal of Medical Research, 2013)
A 33-yr old African female, living in Makkah, presented to ER with decreased LOC & diarrhea which was observed by the attending nurse with no more available history. On examination: she was afebrile, Pulse rate was 100 bpm, BP 90/60 mmHg, R/R 18 breaths/min, O2 sat. 98% on room air. She was disoriented having hallucination, underweight, dehydrated, pale. She was diagnosed as acute confusional state, and she received IVF, PRBC, correction of electrolytes. Pt has received empirical antibiotics since admission and for 3 days, and conservative treatment but has not improved yet. On the 4th day of admission, niacin deficiency was suspected. Therefore, niacin was started at dose of 100 mg BID per oral. By the 6th day of the hospital stay, pt had become oriented, communicating, with no diarrhea, and the skin lesion started to improve. In conclusion, this case calls attention to pellagra when considering the differential diagnosis of hallucination and over salivation.